Carotico-Cavernous Fistula Presenting with Proptosis of Contralateral Eye: A Case Report (Nepalese Journal of Radiology, 2012)
Spontaneous carotico-cavernous fistula occurring post partum is a rare entity. We report a rare case of post partum spontaneous carotico-cavernous fistula with paradoxical proptosis of contralateral eye confirmed by computed tomography and cerebral angiography. NJR I VOL 2 I ISSUE 1 54-56 Jan-June, 2012 DOI: http://dx.doi.org/10.3126/njr.v2i1.6983